2010
DOI: 10.1002/app.33032
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between creep, shrinkage, and dynamic mechanical characteristics of magnetic tape materials

Abstract: Creep compliance, shrinkage, and dynamic mechanical analysis (DMA) results are presented and discussed for developmental magnetic tapes made from PEN and metalized PET (Spaltan V R ) substrates as well as PEN substrate samples cut from wide-stock in the machine and transverse directions. Curve fit parameters from the Kelvin-Voigt model are discussed to shed light on the creepcompliance characteristics, particularly the roll-off characteristics observed at elevated temperatures and long time periods. Characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 91 publications
(181 reference statements)
3
31
0
Order By: Relevance
“…A model with a larger number of parameters is capable of capturing the characteristic roll-off behavior observed for PEN-based tapes and substrates, which could be attributed to relaxation characteristics of the polymer and/or shrinkage. 3,4 Figure 17, showing the radial stress in the wound roll as a function of nondimensional radial position for a seven-parameter model of LTO3, illustrates the effect of the increased stress described by the sevenparameter model at long time ranges. The stress fields in the wound roll are also predicted to increase in stress at long times.…”
Section: Viscoelastic Wound Roll Results For Three- Five- and Sevenmentioning
confidence: 98%
See 2 more Smart Citations
“…A model with a larger number of parameters is capable of capturing the characteristic roll-off behavior observed for PEN-based tapes and substrates, which could be attributed to relaxation characteristics of the polymer and/or shrinkage. 3,4 Figure 17, showing the radial stress in the wound roll as a function of nondimensional radial position for a seven-parameter model of LTO3, illustrates the effect of the increased stress described by the sevenparameter model at long time ranges. The stress fields in the wound roll are also predicted to increase in stress at long times.…”
Section: Viscoelastic Wound Roll Results For Three- Five- and Sevenmentioning
confidence: 98%
“…Other types of relaxation could be occurring in Tape C, which could be attributed to the coating process. 4 For the LTO3 tape shown in Figure 4, with parameters listed in Table I, there is a similarity between the three-and five-parameter Kelvin-Voigt models when compliance, retardation time, and viscosity parameters are compared. However, the sevenparameter model is a better fit for the data during the 10-100 h time period for the LTO3 tape.…”
Section: Experimental Testing Of Polymer Tapementioning
confidence: 88%
See 1 more Smart Citation
“…Rummel and Weick describe the need for ULDMA due to transitions observed in magnetic tape materials at near‐room temperature conditions. Weick also observed these transitions in earlier work using commercial DMA equipment, and noted that such transitions could lead to problems with archival storage of magnetic tapes due to changes in stress‐strain characteristics as the tape is stored in a roll. The investigation was therefore carried‐out using temperatures in the 25–70°C range, and frequencies of 0.006–0.065 Hz within this temperature range.…”
Section: Introductionmentioning
confidence: 85%
“…Previous studies have shown that creep compliance data obtained using LTO3 and developmental tape products [7] can be used as input to an isotropic viscoelastic model which can predict the evolution of the wound-in tape stresses over time. In the previous work, the parameters that describe the tape material (namely, the creep compliance and viscosity parameters) are used to describe the behavior of the roll in the radial direction.…”
Section: Introductionmentioning
confidence: 99%